TINJAUAN YURIDIS TERKAIT PELELANGAN BARANG SITAAN YANG DILAKUKAN OLEH KPK (DIKAITKAN DENGAN PERATURAN PEMERINTAH NOMOR 105 TAHUN 2021 TENTANG LELANG BENDA SITAAN KOMISI PEMBERANTASAN KORUPSI) - Albert Sembiring; Yohana Br Manik (Res Justitia : Jurnal Ilmu Hukum, 2022)
Auction is the sale of goods that are open to the public carried out by/or before the Auction Officer by means of establishing competitive prices and transparency. In the implementation of the auction, there are often obstacles to confiscated goods, including damage, a decrease in economic value, and the cost of confiscation can be too high, so that it can harm the interests of the suspect/defendant as well as the interests of the state. Therefore, Government Regulation Number 105 of 2021 concerning Auction of Confiscated Objects from the Corruption Eradication Commission was made, which allows the KPK to conduct auctions from the investigation stage, so that this provision can be an effective and efficient effort in preventing the above obstacles. The approach method used in this research is normative juridical in the form of analytical descriptive which basically describes the problem being studied, then analyzed with existing legal regulations. The results of the study will show what kinds of goods can be auctioned by the KPK and how the auction is carried out by the KPK